Teachings of Islam for Peaceful Coexistence: Lessons for Conflict Resolution in Pakistani Society (Khairulummah, 2023)
Pakistan since its independence has faced various incidents of violence against minorities and people of different faiths. Political instability, dictatorships, conflicts with neighboring India, conflicts in Afghanistan and militancy in Baluchistan province has always been a threat to stability and development in Pakistan. During the cold war era, the interpretations of the teachings of Islam influenced by political gains have caused widespread problems in our society and specifically the war-ridden areas. The consequences of which we are bearing even till today. This study will have an overview of the history of violence and conflicts in Pakistan, and the underlying causes of these conflicts. This research investigates the historical data from the teachings of Islam and the conflict resolution illustrations from the life of the Prophet of Islam, Peace be upon him.